A practical composite risk score for the development of HUS from STEC infection. (13th November 2019) - Hamilton, D; Cullinan, J
Abstract: Background: Haemolytic Uraemic Syndrome (HUS) is a serious complication of Shiga toxin-producing Escherichia coli (STEC) infection and the key reason why intensive health protection against STEC is required. However, although many potential risk factors have been identified, accurate estimation of risk of HUS from STEC remains challenging. Therefore, we aimed to develop a practical composite score to promptly estimate the risk of developing HUS from STEC. Methods: This was a retrospective cohort study where data for all confirmed STEC infections in Ireland during 2013-15 were subjected to statistical analysis with respect to predicting HUS. Multivariable logistic regression was used to develop a composite risk score, segregating risk of HUS into very low risk (0-0.4%), low risk (0.5-0.9%), medium risk (1.0-4.4%), high risk (4.5-9.9%) and very high risk (10.0% and over). Results: There were 1, 397 STEC notifications with complete information regarding HUS, of whom 5.1% developed HUS. Young age, vomiting, bloody diarrhoea, Shiga toxin 2, infection during April to November, and infection in Eastern and North-Eastern regions of Ireland, were all statistically significant independent predictors of HUS. Demonstration of a risk gradient provided internal validity to the risk score: 0.2% in the cohort with very low risk (1/430), 1.1% with low risk (2/182), 2.3% with medium risk (8/345), 3.1% with high risk (3/98) and 22.2% with very high risk (43/194) scores, respectively, developed HUS. Conclusions: We have developed a composite risk score which may be of practical value, once externally validated, in prompt estimation of risk of HUS from STEC infection. Key messages: We have identified vomiting, bloody diarrhoea, age <10 years, Shiga toxin 2, STEC infection during April-November and in the East/North-East of Ireland as independent predictors of HUS. Using these variables we have developed a practical composite risk score that could be used by clinicians and public health teams to promptly assess the risk of HUS from STEC infection.